2021
DOI: 10.47000/tjmcs.905508
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Covid-19 Infection Cases and Vaccine in 5 Countries Highly Vaccinations

Abstract: COVID-19 has become the most important and crucial agenda in the world in the last year. COVID-19 has taken many lives around the world and millions of people have been infected. To get rid of this depression caused by COVID-19, many countries have started big campaigns for vaccine production. In this study, data on infection cases and vaccinations conducted in England, Germany, Israel, Russia, and the USA were analyzed from January 3, 2020, to March 3, 2021. We used univariate time series models, where the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The aim of this study is to estimate the size of the COVID-19 pandemic for the 15, 30, and 60 days with the ideal forecasting analysis methods by using the daily reported cumulative cases of Germany, Brazil, UAE, UK and Turkey. When the literature was examined, similar studies were found that predicted the COVID-19 epidemic trends [17,[19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study is to estimate the size of the COVID-19 pandemic for the 15, 30, and 60 days with the ideal forecasting analysis methods by using the daily reported cumulative cases of Germany, Brazil, UAE, UK and Turkey. When the literature was examined, similar studies were found that predicted the COVID-19 epidemic trends [17,[19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have used mathematical epidemiological models to analyze the transmission dynamics of COVID -19. SIR is one of the most commonly used mathematical epidemiological models [12]. Covid-19 data from seven countries-China, South Korea, Italy, Spain, Brazil, Germany, and France during the period from February to July 2020 are modeled using machine learning methods, SIR, and a time window SIR (TW-SIR) prediction model [13].…”
Section: Introductionmentioning
confidence: 99%